Development and Application of Physics Learning Video Based on Problem Based Learning with Canva Application to Improve Process Skills - Anggelia, Della; Irwan Koto; Desy Hanisa Putri (Jurnal Penelitian Pembelajaran Fisika, 2025)
This study aims to develop and apply Problem Based Learning (PBL)-based instructional videos using the Canva application and to determine the extent of the improvement in students' process skills on the topic of quantities and measurements, as well as to understand students' responses to the physics instructional videos. The research method used was Research and Development (R&D) with the 4D model (Define, Design, Develop, Disseminate). The research subjects consisted of 33 tenth-grade students from class X9 at SMAN 3 Bengkulu Tengah. Product validation by experts indicated moderate to high validity in the aspects of visuals, audio, content, and language, suggesting that the instructional videos are suitable for development. The implementation results showed an improvement in students' process skills, with an N-Gain score of 0.60, categorized as moderate. Students' responses to the instructional media were categorized as very positive, with an average score of 88.44%. This media is expected to provide an innovative solution for more engaging and effective physics learning.